2013
DOI: 10.1160/th12-12-0907
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of rivaroxaban anticoagulation by haemostatic agents in rats and primates

Abstract: Rivaroxaban is an oral, direct factor Xa inhibitor for the management of thromboembolic disorders. Despite its short half-life, the ability to reverse rivaroxaban anticoagulation could be beneficial in life-threatening emergencies. The potential of prothrombin complex concentrate (PCC; Beriplex®), activated PCC (aPCC; FEIBA®) or recombinant activated factor VII (rFVIIa; NovoSeven®) to reverse rivaroxaban in rats and baboons was investigated. Anaesthetised rats pre-treated with intravenous rivaroxaban (2 mg/kg)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(26 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…In rivaroxaban-anticoagulated human volunteers, e.g., the PT normalized completely upon treatment with PCC [106]. In contrast, PT correction was only partial in rivaroxaban-anticoagulated animals receiving PCC [107,108]. In PT, extent of reversal is dependent on NOAC concentration, NOAC type, PCC dose and used thromboplastin reagent [32,68].…”
Section: Introductionmentioning
confidence: 99%
“…In rivaroxaban-anticoagulated human volunteers, e.g., the PT normalized completely upon treatment with PCC [106]. In contrast, PT correction was only partial in rivaroxaban-anticoagulated animals receiving PCC [107,108]. In PT, extent of reversal is dependent on NOAC concentration, NOAC type, PCC dose and used thromboplastin reagent [32,68].…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy of recombinant factor VIIa and prothrombin complex concentrates and activated prothrombin concentrates on bleeding was evaluated in rats only. 48 …”
Section: Rivaroxaban (2011; Nda 202439 and 22406)mentioning
confidence: 99%
“…Reduced tail bleeding time but not blood loss 25,29 Improvement in exogenous thrombin potential and lag time 27,30 rFVIIa Failed to correct abnormal thrombin generation 40 Reduced tail bleeding time but not blood loss 25,29 Improvement in exogenous thrombin potential and lag time 27,30 Apixaban PCC Improved thrombin generation 31 Improved laboratory parameters but no effect on blood loss 32 No evidence aPCC Improved thrombin generation, clotting time, and clot formation time 31 No evidence No evidence rFVIIa Improved thrombin generation, clotting time, clot formation time, and platelet deposition 31 Reduced bleeding time but no effect on blood loss in rabbits 32 No evidence Rivaroxaban PCC Demonstrated some improvement in PT, clotting time, and thrombin potential but not as effective as aPCC or rFVIIa. 33 Different studies demonstrated no change 34 or only improvement in thrombin generation 35 Reduced PT and bleeding time in rats and baboons 36 Improvement in laboratory parameters including PT and thrombin potential 26,27 Four factor concentrate reduces the PT >3 factor but 3 factor improves thrombin generation more …”
Section: Apixabanmentioning
confidence: 99%